Phosphatidylinositol-4,5-Biphosphate (PI(4,5)P2) Is Required for Rapid Endocytosis in Chromaffin Cells - Fouad Azizi (14152740) (2020)
Objective. Phosphoinositides play a regulatory role in clathrin-mediated endocytosis. However, their involvement in clathrin-independent endocytosis termed rapid endocytosis (RE), which is the mode of vesicle recycling during neurotransmitter release by transient fusion (known as kiss-and-run), has not been investigated. Here, we used patch-clamp recording of whole-cell membrane capacitance in adrenal chromaffin cells (ACC) to monitor changes of RE kinetics in response to pharmacological alteration of phosphatidylinositol-4,5-biphosphate (PI(4,5)P2) level by phenylarsine oxide (PAO) or antibody against phosphatidylinositol 4-kinase (AbPI4K). Results. We found that PAO and AbPI4K significantly abrogated RE kinetics. Infusion of PI(4,5)P2 through the patch pipette potentiated RE kinetics and reversed PAO- and AbPI4K-induced blockade of RE. Similarly, the application of the bifunctional thiol dithiothreitol (DTT) to PAO-treated cells completely prevented the inhibitory effect of PAO on RE. These findings indicate that PI(4,5)P2 is implicated in the signaling (mechanistic) process of RE in ACC. Other information  Published in: BioMed Research International License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1155/2020/9692503